Canine Soft Tissue Sarcomas: Can Being a Dog’s Best Friend Help a Child? - Séguin, Bernard (Frontiers in Oncology, 2017)
Soft tissue sarcomas (STSs) remain a therapeutic challenge for pediatric and adolescent and young adult (AYA) patients. Still today, surgery, radiation therapy, and chemotherapy remain the mainstay of treatment. Obstacles in developing new treatment approaches to improve the outcome are few patients to enroll in clinical trials, and the diversity of tumor biology between histologic subtypes. Pet dogs may offer an additional strategy to discover and test new therapeutic avenues. The number of dogs diagnosed with a STS each year in the United States is estimated to be around 27,000 to 95,000. In comparison, approximately 900 children less than 20 years-old and 1500 AYAs between 15 and 29 years-old are diagnosed with a STS each year in the United States. The mainstay for treatment of STSs in dogs is also surgery, with radiation therapy and chemotherapy when necessary. Similarly to what is seen in humans, grade and stage are prognostic in dogs. In one comparative study of the histology and immunohistochemistry of canine STSs, most tumors were diagnosed as the human equivalent of undifferentiated sarcoma, spindle cell sarcoma, or unclassified spindle cell sarcoma. But much work remains to be done to fully assess the validity of canine STSs as a model. Gene expression analysis has been done in a limited number of canine STSs. Tissue banking, development of cell lines, and the ability to mobilize large scale clinical trials will become essential in veterinary medicine to benefit both dogs and humans.